The existence of Awig – Awig Bali Traditional Village regarding legality principles in National Criminal Law - Desak Made Rai Ningsih; Made Warka; Slamet Suhartono; Otto Yudianto (Technium Social Sciences Journal, 2021)
The type of research used in this research is normative legal research, also commonly called doctrinal legal research or library research, so the approaches used are the statutory approach, conceptual approach, philosophical approach, and case approach. The existence of awig-awig isn’t only determined by the existence of a sense of belonging and recognition from the soul of the community (Volkgeist), but must also comply with the laws and regulations, basic principles of human rights, and applicable state law. Indonesia is a state of law (rechtstaat) by prioritizing legal certainty, so that an independent legal symbol is under the authority of one door, namely the national court. The existence of awig-awig as a symbol of recognition of the existence of customary law community units has been constitutionally recognized as regulated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and even in Law No. 48-2009, judges are obliged to explore, follow and understand the values of customary law, especially awig-awig in Traditional Villages in Bali.